Transformational Leadership and Its Impact on the Psychological Well-being of School Members - Purwanti, Juliastuti; Santosa, Achadi Budi; Zuhaery, Muhammad; Uye, Emmanuel Etim (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to explore the role of madrasah principals in creating a work environment that supports the psychological well-being of madrasah members. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. Thematic analysis revealed that transformational leadership practices, including exemplary behavior, spiritually based motivation, openness to innovative ideas, and personal attention, significantly contribute to a harmonious and supportive work environment. Madrasah principals also facilitate career development, provide emotional support, and ensure adequate facilities, which strengthen dimensions of psychological well-being, including positive interpersonal relationships, autonomy, personal growth, and a clear sense of purpose in life. These findings highlight that integrating transformational leadership with spiritual values not only fosters a positive madrasah climate but also contributes to long-term teacher commitment and educational quality. This study contributes to the literature by demonstrating how leadership practices concretely influence psychosocial dynamics in madrasahs, filling a gap in previous studies that often only emphasize the perspective of stress and burnout.